PI3K Signaling in Cancer: Beyond AKT - Lien, Evan C. (Curr Opin Cell Biol, 2017)
The phosphoinositide 3-kinase (PI3K) signaling pathway is one of the most frequently altered pathways in human cancer and has a critical role in driving tumor initiation and progression. Although PI3K and its lipid product phosphatidylinositol-3,4,5-trisphosphate (PIP(3)) have been shown to activate multiple downstream signaling proteins, the vast majority of studies have focused on the protein kinase AKT as the dominant effector of PI3K signaling. However, recent studies have demonstrated many contexts under which other PIP(3)-dependent signaling proteins critically contribute to cancer progression, illustrating the importance of understanding AKT-independent signaling downstream of PI3K. Here, we highlight three PI3K-dependent, but AKT-independent, signaling branches that have recently been shown to have important roles in promoting phenotypes associated with malignancy. First, the PDK1 -mTORC2-SGK axis can substitute for AKT in survival, migration, and growth signaling and has emerged as a major mechanism of resistance to PI3K and AKT inhibitors. Second, Rac signaling mediates the reorganization of the actin cytoskeleton to regulate cancer cell migration, invasion, and metabolism. Finally, the TEC family kinase BTK has a critical role in B cell function and malignancy and represents a recent example of an effective therapeutic target in cancer. These mechanisms highlight how understanding PI3K-dependent, but AKT-independent, signaling mechanisms that drive cancer progression will be crucial for the development of novel and more effective approaches for targeting the PI3K pathway for therapeutic benefit in cancer.